The economics of gasoline prices in Singapore. - Chen, Jinqi. (2009)
Caltex, ExxonMobil, Shell and Singapore Petroleum Company allege that collusion is not present in Singapore retail gasoline market. In this paper, we examine if this is true by reviewing theories and research papers, studying the firms’ behavior, observing their gasoline prices extracted online from Petrol Watch Singapore’s website and proposing a hypothesis testing to examine for tacit collusion. We observed that Singapore retail gasoline market is functioning as an oligopoly, characterized with a kinked demand curve due to price rigidity, with few competing firms (four firms) selling gasoline that are differentiated with various names and functions, and each firm earning huge amount of profits annually. Observations have also shown price signaling, with either Shell or Caltex always initiating a price change. There might be hint of price manipulation by the four firms through price-leadership strategy. Although price data are publicly available, due to commercial sensitivity, we are unable to gather costs data to provide empirical evidence to support our assumption. Even if Singapore retail gasoline market seems to operate like an oligopoly, our cursory evidence based on frequency and trend analysis of the price data does not support this observation empirically. From here, we can conclude that Singapore retail gasoline market is oligopolistic by structure, but in reality, it appears not to be.